Advanced Retrofitting Solutions for RC Slabs: CFRP, ECC, and Steel Plate Comparison - Eid, Fatma M.; Sedawy, Ahmed E.; Mahmoud, Islam Ali (Civil Engineering Journal, 2025)
Retrofitting reinforced concrete (RC) slabs is crucial for enhancing their flexural strength, ductility, and durability, particularly in aging or seismically deficient structures. This study aims to evaluate and compare the effectiveness of three retrofitting techniques: steel plate bonding, carbon fiber reinforced polymer (CFRP) sheets, and engineered cementitious composites (ECC) with expanded steel mesh in improving the structural behavior of RC slabs. The research integrates both experimental testing and numerical analysis using ABAQUS finite element modeling to assess load–deflection behavior, failure mechanisms, and strength enhancement. The findings revealed that the use of CFRP sheets and ECC with expanded mesh significantly improved the slabs’ structural performance, increasing ultimate load capacity by up to 58% and ductility by more than 40% compared to the control specimens. Conversely, steel plate retrofitting showed inferior performance due to inadequate interfacial bonding. The numerical results exhibited strong agreement with the experimental data, with an average FEM-to-test ratio of 1.04. The study highlights the superior efficiency of CFRP and ECC techniques in strengthening RC slabs, offering enhanced deformation capacity, energy dissipation, and overall seismic resilience, which contributes to the ongoing development of sustainable and high-performance rehabilitation strategies for concrete structures.